Evaluating drug use patterns among paediatric outpatients in Burundi - Audace Manirakiza; David Gitonga Nyamu; Shital Mahindra Maru; Thomas Bizimana; Manassé Nimpagaritse (Taylor & Francis Group, 2024)
ABSTRACTBackground Rational prescribing is key to optimising therapeutic outcomes and avoiding risks associated with irrational use of medicines. Using WHO drug use indicators, this study evaluated drug use patterns among paediatric outpatient encounters at Primary Healthcare Centers (PHCs) in Bujumbura Mairie, Republic of Burundi.Methods Descriptive cross-sectional research assessed paediatric medicine use in 20 PHCs. From 8 February to 7 April 2023, 800 randomly selected paediatric encounters' 2022-year data were retrospectively collected. Data for specific facility indicators were prospectively collected. SPSS 23 was used to analyse data.Results 800 outpatient child encounters were analysed, 48.4% female and 51.6% male. The mean number of medicines per encounter was 2.4(±0.99). The injection rate was 9.9%. Overall, 78.8% of generics and 85.2% of essential medicines were prescribed. Results show drug prescribing differences between private and government PHCs (p < 0.001). All PHCs studied had no standard treatment guidelines (STGs), while 50% had an essential medicine list (EML) and 85% of key medicines were available.Conclusion Poor prescribing practices were found indicating the need for interventions to promote good drug use practices. A large study at a national scale is required to provide a more comprehensive understanding of the overall drug use practices.